Quality Improvement for Steel Wire Coating by the Hot-Dip Galvanizing Process to A Class Standard: A Case Study in a Steel Wire Coating Factory - Ruksorn, Pongthorn; Sudasna-na-Ayudthya, Prapaisri (Agriculture and Natural Resources, 2013)
Demand for steel wire zinc coating by galvanizing to the A class standard is increasing because it protects the wire rod from corrosion. It can be applied to various types of products used in electrical equipment and construction. There are several factors and their levels in the hot-dip galvanizing process that affect the quality of A class galvanized steel wire such as the zinc bath temperature and withdrawal speed. If these factors and their levels are not properly controlled, the mass of zinc coating used will be more than the required standard (greater than 259 g.m-2). The objective of this research was to apply a 2k split-plot experiment to study the effects of factors on the hot-dip galvanizing process to the A class standard. The results showed that the interaction between the zinc bath temperature with each of the charcoal wiping condition, the free zinc length and the withdrawal speed, and the interaction between the charcoal wiping condition and each of the free zinc length and the withdrawal speed significantly affected the mass of zinc coating in the hot-dip galvanizing process to the A class standard. Thus, the appropriate settings were determined to reduce the mass of zinc coating. The confirmation results indicated that after applying the new settings, the mass of zinc coating conformed to the required standard.